2006
DOI: 10.1177/0165025406071491
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of depressive moods and delinquency in early adolescence: The role of failure expectations, manipulativeness, and social contexts

Abstract: This study examined the co-occurrence of depression and delinquency in early adolescents, focusing on longitudinal associations with failure expectations and manipulativeness, and on perceptions of relationships with parents, school and teachers, and peers. Data were used from 1,059 Swedish adolescents aged 13 to 15, who participated in 2 waves (T1–1998; T2–2000) of an ongoing longitudinal research. Results showed that depression and delinquency co-occurred in about 9% of respondents, and that depression and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
(44 reference statements)
2
19
0
3
Order By: Relevance
“…Items were rated on a scale ranging from 1 ( not at all ) to 4 ( often ). Adolescents completed 10 items describing manipulativeness (Overbeek, Biesecker, Kerr, Stattin, Meeus, & Engels, 2006). Items were rated on a scale ranging from 1 ( does not apply to me at all ) to 4 ( applies to me very well ).…”
Section: Methodsmentioning
confidence: 99%
“…Items were rated on a scale ranging from 1 ( not at all ) to 4 ( often ). Adolescents completed 10 items describing manipulativeness (Overbeek, Biesecker, Kerr, Stattin, Meeus, & Engels, 2006). Items were rated on a scale ranging from 1 ( does not apply to me at all ) to 4 ( applies to me very well ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have confirmed the role of failure anticipation in the development of depressive symptoms. In one study, failure anticipation among early adolescents predicted increased depressive symptoms over a 2-year period (Overbeek et al, 2006). In another, failure anticipation and depressive symptoms were shown to be bidirectionally positively associated in middle adolescence across 18 months while controlling for pessimistic cognitions and depressogenic attributions (Määttä et al, 2007).…”
Section: Mechanisms Underlying Peer Contagionmentioning
confidence: 97%
“…By dwelling on these off-task behaviors, the likelihood of actual failure increases over time, thereby enhancing self-deprecating thoughts and pessimism about one's personal future (Määttä et al, 2007;Nurmi, 1993). Youths with high failure anticipation, thus, get trapped in a vicious cycle of self-handicapping behaviors, which increase depressive feelings and thoughts over time (Nurmi, 1997;Overbeek et al, 2006). In sum, adolescents' failure anticipation may lead to depressive symptoms because it increases the risk of becoming trapped in a cycle of self-handicapping behaviors.…”
Section: Mechanisms Underlying Peer Contagionmentioning
confidence: 99%
“…Although internalizing and externalizing problem behaviors are conceptualized as distinct, a large body of literature derived from cross-sectional and longitudinal investigations consistently finds that they are closely related and commonly co-occur (Gilliom and Shaw 2004;Lilienfeld 2003;Oland and Shaw 2005;Overbeek et al 2006). Children exhibiting high levels of delinquent behaviors are also at risk for depressive symptoms, and vice versa (Sheidow et al 2008;Ybrandt 2008).…”
Section: Introductionmentioning
confidence: 99%